2014
DOI: 10.1007/s00384-014-2091-8
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of surgical interventions for high cryptoglandular perianal fistula

Abstract: The best surgical treatment for high cryptoglandular perianal fistulas could not be identified. More randomized controlled trials are needed to find the best treatment. The mucosa advancement flap is the most investigated technique available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
104
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(109 citation statements)
references
References 35 publications
0
104
0
5
Order By: Relevance
“…In another RCT, comparing an acellular dermal matrix (ADM) plug vs ERAF, a healing rate of 82% was reported in the ADM group, with lower rates of recurrence (ADM plug 4% vs ERAF 28%) . A subsequent meta‐analysis comparing the plug with ERAF failed to show any difference in recurrence rates or complications . However, a recent robust multicentre RCT of 94 patients with a transsphincteric fistula demonstrated clinical healing at 12 months in only 38% (15 of 44 patients) treated by collagen plug, compared with 66% (27 of 41 patients) treated by ERAF .…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In another RCT, comparing an acellular dermal matrix (ADM) plug vs ERAF, a healing rate of 82% was reported in the ADM group, with lower rates of recurrence (ADM plug 4% vs ERAF 28%) . A subsequent meta‐analysis comparing the plug with ERAF failed to show any difference in recurrence rates or complications . However, a recent robust multicentre RCT of 94 patients with a transsphincteric fistula demonstrated clinical healing at 12 months in only 38% (15 of 44 patients) treated by collagen plug, compared with 66% (27 of 41 patients) treated by ERAF .…”
Section: Treatmentmentioning
confidence: 99%
“…Benefits in favour of the fistula plug include ease of use and lack of complications. No differences in complication rates have been reported between ERAF and AFP [181], with documented complications including sepsis/abscess, recurrence and constipation [183,185,186]. Unlike some other techniques, no study has reported a detrimental effect to continence following use of a plug.…”
Section: Recommendationsmentioning
confidence: 99%
“…Surgeons regarded physical aspects such as continence, cure and sepsis as being most likely to affect quality of life whereas patients regarded psychological health, independent activity and pain as more important. These findings were confirmed by G€ ottgens et al [18], who conducted a systematic review and meta-analysis of surgical interventions for high cryptoglandular perianal fistula. The authors were criticized because quality of life data either were not extractable or were simply not reported in the various studies.…”
Section: O196mentioning
confidence: 56%
“…These findings were confirmed by Göttgens et al . , who conducted a systematic review and meta‐analysis of surgical interventions for high cryptoglandular perianal fistula. The authors were criticized because quality of life data either were not extractable or were simply not reported in the various studies.…”
Section: Discussionmentioning
confidence: 99%
“…Аноректальный свищ, или хронический парапроктит, -результат воспаления па-раректальной клетчатки, в 90-95% случаев имеющий криптогландулярное происхож-дение, в 3,5% -травматическое, в 1,5% -связанное с болезнью Крона [1].…”
Section: рефератunclassified